Seasonal variation in wool growth rate of Awassi sheep in Iraq - AL-JASSIM, R A M; A HASSAN, ASHWAQ A; ALKASS, J E (The Indian Journal of Animal Sciences, 2013)
Monthly variation in wool growth rate and fibre diameter were studied in 18 Awassi rams of 18 months of age and 47.6 Â± 0.89 kg (mean Â± SE) in body weight (BW). Rams Were maintained under aconstant feeding level (2.5 % of BW) during the whole experimental period (12 months). Wool growth rate (mg/cm2/d) was measured by mid-side patch technique and the fibre diameter by Sonic Fineness Tester. Wool growth rate.ranged between 0.612 and 0.192 mg/cm2/d with two peaks being recorded during August (0.788) and February (0.192). Differences were statistically significant (P< 0.05). Fibre diameter averaged 34 mm. The correlation coefficients between wool growth rate and each of ambient temperature (oC), day length (hr), BW, fibre diameter, were respectively 0.16 (NS), 0.32 (NS), 0.26 (NS) and 0.88 (P